A new species of Jomine Graf-Kumagai (Hymenoptera: Ichneumonidae: Campopleginae) from Brazil - Fabian Herrera-Florez, Andres; Geraldo, Mariana; Filho, Manoel Martins Dias; Penteado-Dias, Angelica (Zootaxa, 2017)
The genus Jomine Graf-Kumagai has two described species known only from Brazil. A new species, J. paulista Herrera-Florez sp. n. is described and its host is given here. The material used in this work was obtained during a survey of the Geometridae larvae and their parasitoids in an understory at São Paulo, Brazil. An identification key to the species of Jomine is provided.